Discussing the Initial Temperature Difference Correction Method for Vibrational Chord Strain Gauge in Bridge Construction Monitoring. Issue 2 (2nd April 2016) - Yang, Jun; Zhang, Hong; Zhou, Jianting; Xu, Bojian; Shan, Aicheng
Abstract: Strain monitoring is an important part of the bridge construction monitoring. The strain obtained from field measurements is usually affected by a variety of factors, an important one of which is temperature difference between the initial temperature and measured temperature. Based on the in-depth introduction of vibrational chord strain gauge's working principle, this part of error is analyzed. Through experiments, it is found that there is a significant linear relationship for initial temperature difference effect. On this basis the temperature difference correction fitting values are calculated and linear regression model is established for analysis. Finally, a field project application for a continuous rigid-frame bridge in Province Yunnan, China was conducted, and the results showed that using strain test fitting values to revise, the calculated stress is quite close to the theory one of structure. This correction method effectively eliminated this part of strain caused by temperature difference.